The London Eye Mystery - Dowd, Siobhan (Oxford ; David Fickling Books, 2008)
When Ted and Kat's cousin Salim disappears from the London Eye ferris wheel, the two siblings must work together--Ted with his brain that is "wired differently" and impatient Kat--to try to solve the mystery of what happened to Salim.
Accelerated Reader AR
Keywords: Asperger's syndrome -- Fiction; Missing children -- Fiction; Meteorology -- Fiction; Brothers and sisters -- Fiction; Cousins -- Fiction; London (England) -- Fiction; England -- Fiction